Rolling printing electrode silver paste and preparation method and application thereof

By combining micron grades and nano -grade silver powder, special polymer resin and hybrid glass powder in rolling printing electrode silver pulp, the problem of insufficient extension and adhesion of the electrode line is solved, and the electrode high -conductivity, mechanical strength and mechanical strength and mechanical strength and mechanical strength are realized. stability.

CN119381050AActive Publication Date: 2025-01-28ZHAOQING CHENYE ELECTRONICS CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411647376.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-01-28
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

In the manufacturing of electronic components, rolling printed electrode silver paste can easily lead to the expansion of the electrode line width during the printing process, resulting in fishbone-like defects, and insufficient electrode adhesion, which affects the stability and reliability of the electrode.

Method used

It adopts rolling printing electrode silver pulp composed of micromio -grade spherical silver powder, micron -grade silver powder, nano -grade silver powder, special high -molecular resin and hybrid glass powder. Through the combination of these materials, the electrical conductivity, mechanical strength and adhesion are improved.

Benefits of technology

Effectively control the width of the electrode line, avoid the generation of fish bone defects, significantly improve the adhesion of the electrode, and ensure the stability and reliability of the electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005140004650000051
    Figure BDA0005140004650000051
  • Figure BDA0005140004650000052
    Figure BDA0005140004650000052
  • Figure BDA0005140004650000061
    Figure BDA0005140004650000061
Patent Text Reader

Abstract

The invention relates to the technical field of conductive silver paste, in particular to rolling printing electrode silver paste and a preparation method and application thereof. The rolling printing electrode silver paste comprises micron-scale spherical silver powder, micron-scale flaky silver powder, nano-scale flaky silver powder, an organic carrier and glass powder, the organic carrier comprises macromolecular resin composed of nitrocellulose, polyvinyl butyral and polyimide resin, and the glass powder is formed by mixing glass powder Z with the sintering temperature of 600-700 DEG C and glass powder N with the sintering temperature of 650-750 DEG C. The rolling printing electrode silver paste provided by the invention not only can effectively improve the printing performance of the electrode, but also can improve the adhesive force of the electrode and ensure the stability and reliability of the electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of conductive silver paste, and in particular to a rolling printing electrode silver paste and a preparation method and application thereof. Background Art

[0002] As an important material in the manufacture of electronic components, rolling printed electrode silver paste plays a key role in the manufacture of magnetic bead array inductor products. As one of the widely used components in electronic equipment, magnetic bead array is widely used in the fields of DC isolation, coupling, bypass, filtering, tuning circuit, energy conversion, control circuit, etc., such as general electronic circuits such as laptops, motherboards, mobile phones, digital cameras, as well as high voltage circuits, LCD backlight converter circuits, etc.

[0003] As electronic products gradually develop towards miniaturization, the size of magnetic bead array products continues to shrink, and the size requirements of rolling printed electrodes have become more precise. Therefore, the electrode line width caused by rolling printing of electrode silver paste often expands, resulting in fishbone defects, making the size exceed the standard and posing the risk of short circuit in the later stage. In addition, as the electrode line becomes smaller, the requirements for the electrode adhesion formed by the silver paste are also increasing.

[0004] Therefore, as electronic components are becoming increasingly miniaturized and refined, how to ensure the rolling printing quality of electrode silver paste and improve the adhesion of the electrode has become a technical problem that needs to be urgently solved in the field of electronic component manufacturing. Summary of the invention

[0005] In order to ensure the rolling printing quality of electrode silver paste and improve the adhesion of electrodes under the trend of increasingly miniaturized electronic components, the present application provides a rolling printing electrode silver paste and its preparation method and application. The rolling printing electrode silver paste provided by the present application can not only effectively control the electrode line width and avoid the generation of fishbone defects, but also improve the adhesion of the electrode and ensure the stability and reliability of the electrode.

[0006] In the first aspect, the present application provides a rolling printing electrode silver paste adopting the following technical solution: A rolling printing electrode silver paste comprises the following raw materials in percentage by mass: 35%-40% micron-sized spherical silver powder, 25%-35% micron-sized flaky silver powder, 10%-15% nano-sized flaky silver powder, 10%-25% organic carrier and 3%-5% glass powder; The organic carrier is prepared by mixing a polymer resin and an organic solvent in a mass ratio of (1-3): (7-9); The polymer resin is prepared by mixing nitrocellulose, polyvinyl butyral and polyimide resin in a mass ratio of (1-2): (1-2): (0.5-1); The glass powder is formed by mixing glass powder Z with a sintering temperature of 600-700° C. and glass powder N with a sintering temperature of 650-750° C. in a mass ratio of 1:1.

[0007] In the above technical scheme, the present application not only improves the conductivity of the electrode by combining micron-sized spherical silver powder and micron-sized flaky silver powder, but also enhances the mechanical strength of the electrode by the filling effect of the spherical silver powder. The present application further adds nano-sized flaky silver powder, because the nano-sized flaky silver powder has a large specific surface area and can form more contact points with the substrate, thereby enhancing the adhesion between the silver paste and the substrate, thereby further improving the conductivity and adhesion of the electrode. At the same time, the present application adopts a polymer resin prepared by nitrocellulose, polyvinyl butyral and polyimide resin in a specific proportion, through the solubility and adhesion of nitrocellulose, through the mechanical strength and heat resistance of polyvinyl butyral, through the high temperature resistance and chemical stability of the polyimide resin, through these characteristics, the silver paste has better adhesion and stability during the printing process, thereby ensuring the reliability of the electrode. In addition, the present application uses a mixture of glass powder Z with a sintering temperature of 600-700°C and glass powder N with a sintering temperature of 650-750°C, so that the glass powder has good sintering performance at different temperatures, thereby providing a better bonding effect during the electrode formation process, which not only helps to improve the mechanical strength of the electrode, but also improves the heat resistance of the electrode to a certain extent, thereby further enhancing the adhesion and stability of the electrode. Through the above-mentioned optimization of the rolling printing electrode silver paste, the present application can effectively control the electrode line width, avoid the generation of fishbone defects, and significantly improve the adhesion of the electrode.

[0008] Preferably, the mass ratio of the nitrocellulose, polyvinyl butyral and polyimide resin is 2:1:1.

[0009] In the above technical solution, the present application optimizes the mass ratio of nitrocellulose, polyvinyl butyral and polyimide resin to 2:1:1, so that the silver paste has better adhesion and stability during the printing process. Nitrocellulose provides good solubility and adhesion, allowing the silver paste to better adhere to the surface of the substrate; polyvinyl butyral provides the necessary mechanical strength and heat resistance to ensure that the silver paste will not be deformed or damaged during high-temperature sintering; and the high temperature resistance and chemical stability of the polyimide resin further enhance the heat resistance and long-term stability of the silver paste.

[0010] Preferably, the organic solvent is one or more of terpineol, ethylene glycol ethyl ether acetate, ethylene glycol butyl ether acetate, turpentine, and cyclohexanone.

[0011] In the above technical scheme, the present application selects one or more of terpineol, ethylene glycol ethyl ether acetate, ethylene glycol butyl ether acetate, turpentine, and cyclohexanone as organic solvents. These solvents have good solubility and volatility, and can ensure that the polymer resin can be fully dissolved and evenly mixed in the process of preparing the organic carrier. At the same time, these solvents can evaporate quickly in the subsequent printing process, reducing the impact on the performance of the electrode silver paste, thereby ensuring the stability and reliability of the electrode silver paste during the printing process.

[0012] Preferably, based on the mass fraction of the glass powder Z, the glass powder Z includes 20-30 parts of zinc oxide, 10-20 parts of sodium oxide, 10-20 parts of bismuth trioxide, 15-30 parts of silicon dioxide, 10-20 parts of boron oxide, 5-20 parts of aluminum oxide, 10-20 parts of barium oxide, 1-6 parts of titanium dioxide, 2-6 parts of copper oxide, and 1-10 parts of nickel oxide.

[0013] Preferably, based on the mass fraction of the glass powder N, the glass powder N includes 10-20 parts of zinc oxide, 20-30 parts of sodium oxide, 10-20 parts of bismuth trioxide, 15-30 parts of silicon dioxide, 10-20 parts of boron oxide, 5-20 parts of aluminum oxide, 10-20 parts of barium oxide, 1-6 parts of titanium dioxide, 2-6 parts of copper oxide, and 1-10 parts of nickel oxide.

[0014] In the above technical scheme, the present application specifically defines the composition and ratio of glass powder Z and glass powder N, and fine-tunes the amount of glass powder Z and glass powder N so that glass powder Z and glass powder N can form a uniform glass phase during the sintering process to adapt to a higher sintering temperature range, thereby ensuring the stability of the electrode at different temperatures. The addition of zinc oxide, sodium oxide and bismuth trioxide helps to lower the melting point of the glass, so that the glass powder can still maintain good sintering performance at higher temperatures, thereby ensuring the stability of the electrode at high temperatures. Silicon dioxide, boron oxide and aluminum oxide provide good chemical stability and mechanical strength, ensuring the long-term reliability of the electrode. The addition of barium oxide, titanium dioxide, copper oxide and nickel oxide further optimizes the electrical properties and corrosion resistance of the glass powder, thereby improving the overall performance of the electrode.

[0015] Preferably, the particle size of the glass powder Z is 0.5-2 μm, and the particle size of the glass powder N is 0.5-2 μm.

[0016] In the above technical scheme, the present application ensures the uniform distribution of the glass powder in the electrode by limiting the particle size of the glass powder Z and the glass powder N to 0.5-2μm, thereby forming a uniform glass phase during the sintering process, effectively avoiding the uneven electrode surface or internal stress concentration problems caused by the excessively large glass powder particle size. At the same time, the uniform glass phase can improve the mechanical strength and heat resistance of the electrode, ensuring that the electrode will not crack or deform during the high-temperature sintering process, thereby ensuring the long-term reliability of the electrode.

[0017] Preferably, the particle size of the micron-sized spherical silver powder is 0.6-1 μm, the particle size of the micron-sized flaky silver powder is 1.5-3.5 μm, and the particle size of the nano-sized flaky silver powder is 0.01-0.1 μm.

[0018] In the above technical solution, the present application has carefully designed the particle size distribution of micron-sized spherical silver powder, micron-sized flaky silver powder and nano-sized flaky silver powder to ensure that the silver powder can be evenly distributed during the printing process, thereby reducing the problem of electrode line width expansion.

[0019] In the second aspect, the present application provides a method for preparing a rolling printing electrode silver paste using the following technical solution: A method for preparing a rolling printing electrode silver paste comprises the following steps: Step 1: firstly, mix the organic solvent and the polymer resin evenly to prepare an organic carrier; Step 2: Add the remaining raw materials to the organic carrier and stir under vacuum until the mixture is uniform; Step 3: Grind the slurry obtained in step 2 to a fineness of less than 7.5 μm, filter, and prepare a rolling printing electrode silver paste.

[0020] In the above technical scheme, the present application provides a simple and effective process for preparing the rolling-printed electrode silver paste, which ensures the uniformity and stability of the rolling-printed electrode silver paste.

[0021] In the third aspect, the application of a rolling printing electrode silver paste provided by the present application adopts the following technical solution: The invention discloses an application of rolling printing electrode silver paste, which is to apply the rolling printing electrode silver paste to printing magnetic bead electrodes.

[0022] In the above technical solution, the rolling printing electrode silver paste of the present application has good printing performance and high adhesion, and is particularly suitable for the rolling printing of magnetic bead electrodes, which can effectively avoid the generation of fishbone defects, ensure the accuracy of electrode size, and reduce the risk of short circuit in the later stage. In addition, the rolling printing electrode silver paste of the present application is also suitable for other electronic component manufacturing fields that require high-precision and high-adhesion electrodes.

[0023] In summary, the present application includes at least one of the following beneficial technical effects: 1. The present application combines micron-sized spherical silver powder, micron-sized flaky silver powder and nano-sized flaky silver powder, adopts a polymer resin prepared from nitrocellulose, polyvinyl butyral and polyimide resin, mixes glass powder Z with a sintering temperature of 600-700°C and glass powder N with a sintering temperature of 650-750°C, and optimizes the glass powder composition and particle size to effectively control the electrode line width, avoid the generation of herringbone defects, and significantly improve the adhesion of the electrode.

[0024] 2. The rolling printing electrode silver paste of the present application is suitable for the rolling printing of magnetic bead electrodes, which effectively avoids the generation of herringbone defects, ensures the accuracy of electrode size, effectively improves electrode adhesion, and reduces the risk of short circuit in the later stage. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a picture of the printed electrode of the rolling printed electrode silver paste of Example 1.

[0026] Figure 2 This is a picture of the printed electrode of the rolling printed electrode silver paste of Example 2.

[0027] Figure 3 This is a picture of the printed electrode of the rolling printed electrode silver paste of Example 3.

[0028] Figure 4 This is a picture of the printed electrode of the rolling printed electrode silver paste of comparative example 1.

[0029] Figure 5 This is a picture of the printed electrode of the rolling printed electrode silver paste of comparative example 2.

[0030] Figure 6 This is a picture of the printed electrode of the rolling printed electrode silver paste of comparative example 3.

[0031] Figure 7 This is a picture of the printed electrode of the rolling printed electrode silver paste of comparative example 4.

[0032] Figure 8 This is a picture of the printed electrode of the rolling printed electrode silver paste of Example 5.

[0033] Fig. 9 This is a picture of the printed electrode of the rolling printed electrode silver paste of Example 6. DETAILED DESCRIPTION

[0034] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.

[0035] Example 1 A rolling printing electrode silver paste comprises micron-level spherical silver powder, micron-level flaky silver powder, nanometer-level flaky silver powder, an organic carrier and glass powder.

[0036] Among them, the micron-sized spherical silver powder is homemade, with a particle size between 0.6-1μm.

[0037] Among them, the micron-sized flaky silver powder is homemade, with a particle size between 1.5-3.5μm.

[0038] Among them, the nano-scale flaky silver powder is homemade, with a particle size between 0.01-0.1μm.

[0039] Among them, the organic carrier is prepared from polymer resin and organic solvent.

[0040] Among them, the polymer resin is composed of nitrocellulose, polyvinyl butyral and polyimide resin.

[0041] The organic solvent is a mixture of pineol and cyclohexanone in a mass ratio of 1:1.

[0042] Among them, the glass powder Z is homemade, and the particle size is between 0.5-2 μm.

[0043] Among them, the glass powder N is homemade, and the particle size is between 0.5-2 μm.

[0044] The method for preparing the rolling printing electrode silver paste comprises the following steps: Step 1: First, completely dissolve the polymer resin in an organic solvent at 60-70°C, and stir until the mixture is uniformly mixed to prepare an organic carrier.

[0045] Step 2: Add the remaining raw materials to the organic carrier and stir under vacuum until the mixture is uniform.

[0046] Step 3: Grind the slurry obtained in step 2 with a three-roll mill to a fineness of less than 7.5 μm, filter, and prepare a roll-printed electrode silver paste.

[0047] Example 2 A rolling printing electrode silver paste, which is different from Example 1 in that the amounts of various raw materials used are inconsistent.

[0048] Example 3 A rolling printing electrode silver paste, which is different from Example 1 in that the amounts of various raw materials used are inconsistent.

[0049] The amounts of the micron-sized spherical silver powder, micron-sized flaky silver powder, nano-sized flaky silver powder, polymer resin, organic solvent, glass powder Z and glass powder N in Examples 1-3 are shown in Table 1.

[0050] Table 1: The raw material ratios of the polymer resins used in Examples 1-3 are shown in Table 2.

[0051] Table 2: The raw material ratios of the glass powder Z used in Examples 1-3 are shown in Table 3.

[0052] Table 3: The raw material ratios of the glass powder N used in Examples 1-3 are shown in Table 4.

[0053] Table 4: Comparative Example 1 A rolling printing electrode silver paste, which is different from Example 1 in that nitrocellulose is replaced by ethyl cellulose in equal amounts.

[0054] Comparative Example 2 A rolling printing electrode silver paste, which is different from Example 1 in that polyvinyl butyral is replaced by acrylic resin in equal amount.

[0055] Comparative Example 3 A rolling printing electrode silver paste, which is different from Example 1 in that the polyimide resin is replaced by acrylic resin in equal amount.

[0056] Comparative Example 4 A rolling printing electrode silver paste, which is different from Example 1 in that the nano-scale flaky silver powder is replaced by micron-scale flaky silver powder in equal amounts.

[0057] Comparative Example 5 A rolling printing electrode silver paste, which is different from Example 1 in that glass powder N is replaced by glass powder Z in equal amount.

[0058] Comparative Example 6 A rolling printing electrode silver paste, which is different from Example 1 in that the glass powder Z is replaced by glass powder N in equal amount.

[0059] Performance testing: Sample: Roll-printed electrode silver paste of Examples 1-3 and Comparative Examples 1-6.

[0060] The sample was prepared according to the conventional preparation process of magnetic bead array inductor to obtain 2012 magnetic bead array inductor, and the printed pattern and adhesion of the magnetic bead array inductor were tested.

[0061] The printed graphics are shown in Figure 1-9.

[0062] Among them, the adhesion test uses a tensile gauge, and the test method is: visual inspection at the minimum tension for 30S, the inspection end is required to be free of damage and fall off, the end tension standard of the CBA magnetic bead array is: 2012≥0.3Kgf, when the tension without damage and fall off reaches the above standard, it is considered qualified. The test results are shown in Table 5.

[0063] Table 5: Combination Figure 1-9 Observation and analysis, Figure 1-3 , Figure 8-9 The printed electrode pictures have qualified appearance. Figure 4 The printed electrodes in the printed electrode pictures are outwardly expanded, with corners exposed and the appearance is unqualified. Figure 5 The magnet in the printed electrode picture is silver-sticky and the appearance is unqualified. Figure 6 The magnet in the printed electrode picture is silver-sticky and the appearance is unqualified. Figure 7 The printed electrodes in the printed electrode picture are outwardly expanded, with stepped edges and corners, and the appearance is unqualified.

[0064] Specifically combining the analysis of the test data of the rolling printed electrode silver paste of Examples 1-3 and Comparative Examples 1-6, it can be seen that Examples 1-3 have good printing performance and adhesion, Comparative Examples 1-4 have good adhesion, and Comparative Examples 5-6 have good printing performance.

[0065] Specifically analyzing in combination with Example 1 and Comparative Examples 1-4, the difference between Comparative Examples 1-4 and Example 1 is that in Comparative Example 1, an equal amount of nitrocellulose is replaced by ethyl cellulose, an equal amount of polyvinyl butyral is replaced by acrylic resin in Comparative Example 2, an equal amount of polyimide resin is replaced by acrylic resin in Comparative Example 3, and an equal amount of nano-scale flaky silver powder is replaced by micron-scale flaky silver powder in Comparative Example 4. Through these comparisons, the present application can find that the use of nitrocellulose, polyvinyl butyral, polyimide resin and nano-scale flaky silver powder has a positive effect on the printing performance and adhesion of the rolling printed electrode silver paste, and can further improve the printing performance and adhesion of the rolling printed electrode silver paste.

[0066] Specifically analyzing in combination with Example 1 and Comparative Examples 5-6, the difference between Comparative Examples 5 and 6 and Example 1 is that glass powder N and glass powder Z are replaced respectively. It can be seen that the combined use of glass powder N and glass powder Z has a certain influence on the adhesion of the rolling printed electrode silver paste. In order to ensure that the rolling printed electrode silver paste of the present application can have good printing performance and adhesion at the same time, it is necessary to add glass powder N and glass powder Z to the rolling printed electrode silver paste at the same time.

[0067] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A rolling printing electrode silver paste, characterized in that: The raw materials include the following mass percentages: 35%-40% micron-sized spherical silver powder, 25%-35% micron-sized flaky silver powder, 10%-15% nano-sized flaky silver powder, 10%-25% organic carrier and 3%-5% glass powder; The organic carrier is prepared by mixing a polymer resin and an organic solvent in a mass ratio of (1-3): (7-9); The polymer resin is prepared by mixing nitrocellulose, polyvinyl butyral and polyimide resin in a mass ratio of (1-2): (1-2): (0.5-1); The glass powder is formed by mixing glass powder Z with a sintering temperature of 600-700° C. and glass powder N with a sintering temperature of 650-750° C. in a mass ratio of 1:

1.

2. The rolling printing electrode silver paste according to claim 1, characterized in that: The mass ratio of the nitrocellulose, polyvinyl butyral and polyimide resin is 2:1:

1.

3. The rolling printing electrode silver paste according to claim 1, characterized in that: The organic solvent is one or more of terpineol, ethylene glycol ethyl ether acetate, ethylene glycol butyl ether acetate, turpentine and cyclohexanone.

4. The rolling printing electrode silver paste according to claim 1, characterized in that: Calculated by mass percentage, the glass powder Z includes 20-30 parts of zinc oxide, 10-20 parts of sodium oxide, 10-20 parts of bismuth trioxide, 15-30 parts of silicon dioxide, 10-20 parts of boron oxide, 5-20 parts of aluminum oxide, 10-20 parts of barium oxide, 1-6 parts of titanium dioxide, 2-6 parts of copper oxide, and 1-10 parts of nickel oxide.

5. The rolling printing electrode silver paste according to claim 1, characterized in that: Calculated by mass percentage, the glass powder N includes 10-20 parts of zinc oxide, 20-30 parts of sodium oxide, 10-20 parts of bismuth trioxide, 15-30 parts of silicon dioxide, 10-20 parts of boron oxide, 5-20 parts of aluminum oxide, 10-20 parts of barium oxide, 1-6 parts of titanium dioxide, 2-6 parts of copper oxide, and 1-10 parts of nickel oxide.

6. The rolling printing electrode silver paste according to claim 1, characterized in that: The particle size of the glass powder Z is 0.5-2 μm, and the particle size of the glass powder N is 0.5-2 μm.

7. The rolling printing electrode silver paste according to claim 1, characterized in that: The particle size of the micron-sized spherical silver powder is 0.6-1 μm, the particle size of the micron-sized flaky silver powder is 1.5-3.5 μm, and the particle size of the nano-sized flaky silver powder is 0.01-0.1 μm.

8. A method for preparing a rolling printing electrode silver paste according to any one of claims 1 to 7, characterized in that: The following steps are involved: Step 1: firstly, mix the organic solvent and the polymer resin evenly to prepare an organic carrier; Step 2: Add the remaining raw materials to the organic carrier and stir under vacuum until the mixture is uniform; Step 3: Grind the slurry obtained in step 2 to a fineness of less than 7.5µm, filter, and prepare a silver paste for rolling printing electrodes.

9. An application of the rolling printing electrode silver paste according to any one of claims 1 to 7, characterized in that: Application of rolling printed electrode silver paste in printing magnetic bead electrodes.

Citation Information

Patent Citations

  • High-strength printed circuit board conductive silver paste and preparing method thereof

    CN103985431A

  • Low-temperature conductive printed circuit board silver slurry and preparation method thereof

    CN103996429A

  • Formula of low-temperature-sintered low-silver content inductor end-coated silver paste and preparation method thereof

    CN106098150A

  • All-aluminum back-field back silver paste, preparation method thereof, and application thereof

    CN109524150A

  • Conductive paste and solar cell

    CN112204676A